HUBUNGAN KINERJA PENYULUH PERTANIAN DENGAN DINAMIKA KELOMPOK TANI DI KELURAHAN MATABUBU KECAMATAN POASIA KOTA KENDARI - Husna, Muflihun Bil; Mappasomba, Musadar; Salahuddin, Salahuddin; Buana, Tjandra (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This research aims to assess the performance of agricultural extension officers and the dynamics of farmer groups, as well as to identify the relationship between these two factors. The population in this study consists of 140 farmers who are members of 9 farmer groups, and the sample in this research includes 35 individuals selected using proportional random sampling. Data for the study was collected through questionnaires and subsequently analyzed quantitatively using class interval formulas and Spearman rank correlation. The results of the study indicate that the performance of agricultural extension officers and the dynamics of farmer groups in Matabubu Village, Poasia District, Kendari City, fall into the high or dynamic category, which implies that the farmer groups have effectively implemented the existing indicators. The performance of agricultural extension officers has a significant and close relationship with the dynamics of farmer groups, with a positive direction in the formed relationship.